2020
DOI: 10.1186/s43141-020-00034-w
|View full text |Cite
|
Sign up to set email alerts
|

Insights from the in silico structural, functional and phylogenetic characterization of canine lysyl oxidase protein

Abstract: Background Lysyl oxidase is an extracellular regulatory enzyme with an imperative role in interlinking of collagen and elastin by oxidizing lysine residues. Lysyl oxidase has been implicated in incidence of mammary tumors in bitches. Therefore, it becomes significant to study the structural and functional features of this enzyme for a better understanding of its molecular mechanisms. Results The detailed computational investigation of the canine lysyl oxidase protein was analyzed in silico with respect to its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…6b). This has been reported in silico for different proteins in different species" [38][39][40][41].…”
Section: Resultsmentioning
confidence: 56%
“…6b). This has been reported in silico for different proteins in different species" [38][39][40][41].…”
Section: Resultsmentioning
confidence: 56%
“…As a result, 86.7% of the residues were located in the most favored regions. According to this resulted percentage, the constructed model is considered to be of good quality [ 47 ]. Molecular docking analysis revealed that carboxymethyl cellulase formed favorable interactions with Bacillus amyloliquefaciens strain elh1-cellulase within the active site of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…They found out that there is a slight possibility that the concerned gene in humans may have evolutionary relationship with that of canines and may be correlated with the cancer progression. (44).…”
Section: Discussionmentioning
confidence: 99%